The interplay of mitochondrial dysfunction and altered metabolic pathways in glioblastoma - Ainun Baharuddin, Wan Noor; Yusoff, Abdul (Contemporary Oncology/Współczesna Onkologia, 2025)
Glioblastoma (GBM) is the most aggressive and lethal primary brain tumor, characterized by rapid progression, treatment resistance, and poor prognosis, with a survival rate of less than five years despite advances in medical interventions. A hallmark of GBM is metabolic reprogramming, which supports tumor growth and progression. Mitochondrial dysfunction plays a critical role in this metabolic shift by altering energy production and disrupting key cellular pathways. However, the precise molecular mechanisms underlying these alterations remain inadequately understood. This review highlights the fundamental contributions of mitochondrial oxidative phosphorylation (OXPHOS) and the electron transport chain (ETC) to GBM pathology. Notably, deficiencies in mitochondrial DNA and its associated molecular components have been identified as key factors contributing to impaired mitochondrial function. Additionally, an imbalance in reactive oxygen species production within the ETC has been implicated in driving cellular and metabolic changes that promote tumor progression. Given the central role of mitochondrial metabolism in GBM, targeting OXPHOS and ETC components presents a promising therapeutic approach. This review also discusses current pharmacological strategies aimed at modulating mitochondrial respiration, with a focus on drugs and compounds that selectively inhibit OXPHOS complexes. Understanding the intricate relationship between mitochondrial dysfunction and GBM progression may provide valuable insights for developing novel therapeutic interventions, ultimately improving clinical outcomes for patients with this devastating disease.